2021
DOI: 10.1186/s12884-021-04272-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-fetal bonding during the COVID-19 pandemic

Abstract: Background The pregnant population experienced unique COVID-19 physical and psychosocial stressors such as direct health concerns related to the virus and loss of access to resources since the COVID-19 emerged as a global pandemic in early 2020. Despite these COVID-19-related stress and concerns, the maternal experience of bonding with their unborn children has not been well studied. This work aimed to study the association between mental health history, current mental health symptoms, psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, research studies exploring the effect of the COVID-19 pandemic on prenatal bonding have focussed predominantly on mothers and are generalised to consider the whole pregnancy experience, including labour and childbirth [20][21][22]. Whilst some do acknowledge antenatal ultrasound as part of the wider analysis, drawing more specific conclusions around the effect of ultrasound scanning during the pandemic on bonding is challenging because of the additional and external moderators.…”
Section: Study Rationale and Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research studies exploring the effect of the COVID-19 pandemic on prenatal bonding have focussed predominantly on mothers and are generalised to consider the whole pregnancy experience, including labour and childbirth [20][21][22]. Whilst some do acknowledge antenatal ultrasound as part of the wider analysis, drawing more specific conclusions around the effect of ultrasound scanning during the pandemic on bonding is challenging because of the additional and external moderators.…”
Section: Study Rationale and Aimmentioning
confidence: 99%
“…optimal bonding score is challenging because whilst a score may be statistically significant within an analysis, this may not represent clinical significance [32]. Previous studies using the MAAS define a threshold of 80% of the global score to differentiate between low and high bonding [9,20]. Using this definition, the average scores of parents completing the modified PAI in this study would be classified as low bonding.…”
Section: Plos Onementioning
confidence: 99%
“…For instance, an international study found that maternal-fetal attachment in high-risk pregnant women was higher than normal pregnant women, and high-risk situations such as high-risk pregnancies increased adaptation to pregnancy and strengthened maternal-fetal attachment [ 39 ]. Furthermore, previous studies have suggested that COVID-19 stress could lead to an increase in maternal-fetal attachment by wanting to care more for the fetus and provide protection [ 40 ]. Childbirth during traumatic situations like the COVID-19 pandemic has also been reported to trigger maternal psychological growth by presenting feelings of gratitude for life and individual capacity, and thus bringing about better mother-infant attachment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Members of perinatal care teams may find it helpful to discuss with patients and families factors that may contribute to maternal stress, including perceptions of prenatal and postpartum support and adaptive, rather than maladaptive, coping mechanisms to mitigate stress related to public health emergencies. As maternal resilience and prenatal stress-response has been shown to be important to fetal and infant bonding 44,45 and child health, [46][47][48] strategies to promote resiliency and healthy coping should be encouraged, including referral to a mental health practitioner. Notably, one-in-ten of our respondents reported being unable to discuss postpartum mood changes and nearly one-fifth of our respondents felt that access to a mental health practitioner was an important form of support during COVID-19.…”
Section: Discussionmentioning
confidence: 99%